2020
DOI: 10.21203/rs.2.22563/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility of an integrated multidisciplinary geriatric rehabilitation programme for older stroke patients: a process evaluation

Abstract: Background: Almost half of the stroke patients admitted to geriatric rehabilitation has persisting problems after discharge. Currently, there is no evidence based geriatric rehabilitation programme available for older stroke patients, combining inpatient rehabilitation with adequate aftercare aimed at reducing the impact of persisting problems after discharge from a geriatric rehabilitation unit. Therefore, we developed an integrated multidisciplinary rehabilitation programme consisting of inpatient neurorehab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 20 publications
0
6
0
7
Order By: Relevance
“…In addition the training of care professionals in conducting the programme could be improved. However, despite this, the majority of patients, informal caregivers and care professionals indicated the bene cial aspects of the programme 25 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition the training of care professionals in conducting the programme could be improved. However, despite this, the majority of patients, informal caregivers and care professionals indicated the bene cial aspects of the programme 25 .…”
Section: Discussionmentioning
confidence: 96%
“…The lack of effect of the programme on daily activity and most secondary outcome measures might be explained by several reasons. First, the process evaluation which was performed alongside the trial, revealed that part of patients and informal caregivers did not receive all key elements of the programme 25 . Although almost all patients formulated rehabilitation goals, the GAS method was only used among two thirds of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of effect of the programme on daily activity and most secondary outcome measures might be explained by several reasons. First, the process evaluation which was performed alongside the trial, revealed that part of patients and informal caregivers did not receive all key elements of the programme 27 . Although almost all patients formulated rehabilitation goals, the GAS method was only used among two thirds of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the percentage of therapy sessions performed in the patients' home environment was lower than planned, and only about a quarter of the patients and informal caregivers attended the education sessions. Furthermore, the self-management training was considered by the care professionals as rather complex and di cult to apply for frail older persons, because it was complicated for the patients to develop and carry out action plans by themselves 27 . As it is widely recognised that in complex interventions often not all aspects of the intervention are completely performed according to protocol and that adaptation to local circumstances may be necessary 28 , it is important to improve the feasibility of the integrated programme by tailoring the goal attainment scaling, self-management training and education sessions more optimally to the population of frail older stroke patients 27 .…”
Section: Discussionmentioning
confidence: 99%